2013
DOI: 10.1071/pc130076
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of black cockatoos at a mine-site in the eastern jarrah-marri forest, western Australia.

Abstract: Three threatened black cockatoos inhabit the Jarrah Eucalyptus marginata-Marri Corymbia calophylla forest of southwestern Australia: Baudin’s Cockatoo Calyptorhynchus baudinii, Carnaby’s Cockatoo C. latirostris, and Forest Redtailed Black Cockatoo C. banksii naso [FRTBC]. Their local ecology in relation to anthropogenic disturbance is poorly known, hampering effective conservation management. Therefore we studied their group size, site occupancy patterns, habitat use, and food plants at a mine-site and its sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As recently as the 1980s RTBC's were considered a rare and seasonal (May to November) visitor to the eastern SCP (Johnstone et al 2018), however, in 2019 the annual Birdlife Australia Great Cocky Count recorded 3499 birds on the highly urbanized coastal plain, a six-fold increase from 601 birds counted in 2014 (Peck et al 2019). Forest clearing is suggested as contributing to increased numbers on the plain, as the species' distribution is predominantly associated with jarrah (Eucalyptus marginata) and marri (Corymbia calophylla) forests, as is the presence of native and non-native food species such as cape lilac (Melia azedarah) (Johnstone et al 2013, Lee et al 2013, Johnstone et.al. 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As recently as the 1980s RTBC's were considered a rare and seasonal (May to November) visitor to the eastern SCP (Johnstone et al 2018), however, in 2019 the annual Birdlife Australia Great Cocky Count recorded 3499 birds on the highly urbanized coastal plain, a six-fold increase from 601 birds counted in 2014 (Peck et al 2019). Forest clearing is suggested as contributing to increased numbers on the plain, as the species' distribution is predominantly associated with jarrah (Eucalyptus marginata) and marri (Corymbia calophylla) forests, as is the presence of native and non-native food species such as cape lilac (Melia azedarah) (Johnstone et al 2013, Lee et al 2013, Johnstone et.al. 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2013aLee et al ( , 2013b observed that black cockatoos used revegetation for feeding, but not roosting, perhaps because of the small size and open canopy of overstorey trees in intermediate-aged revegetation. Cockatoos prefer to roost in taller trees with wider canopies (Johnstone and Kirkby 2008).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Floristics were recorded as the number of species present known to be food plants of the three study species (Table 1), on the basis of Saunders (1974aSaunders ( , 1974bSaunders ( , 1980, Johnstone and Storr (1998), Johnstone and Kirkby (1999), Johnstone et al (2013b) and Lee et al (2013a). To quantify vegetation structure, we measured canopy cover, canopy height and understorey height, and counted stem densities of plant species that are a common food resource for black cockatoos (Banksia spp., Hakea spp., marri and jarrah; Table 1).…”
Section: Revegetation Structure and Floristicsmentioning
confidence: 99%
See 2 more Smart Citations